2023
DOI: 10.3390/ijms24065604
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and Its Fermented Extract as a Potential Inhibitor of Bisphenol A-Exposed HT-29 Colon Cancer Cells’ Viability

Abstract: Bisphenol A (BPA) promotes colon cancer by altering the physiological functions of hormones. Quercetin (Q) can regulate signaling pathways through hormone receptors, inhibiting cancer cells. The antiproliferative effects of Q and its fermented extract (FEQ, obtained by Q gastrointestinal digestion and in vitro colonic fermentation) were analyzed in HT-29 cells exposed to BPA. Polyphenols were quantified in FEQ by HPLC and their antioxidant capacity by DPPH and ORAC. Q and 3,4-dihydroxyphenylacetic acid (DOPAC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Previously, García‐Gutiérrez et al. demonstrated that Quercetin significantly increased the expression of ESR1 in HT‐29 colon cancer cells 59 . Calycosin promoted the expression of ER‐α36, which is the main oestrogen receptor of ESR1, in macrophages 60 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously, García‐Gutiérrez et al. demonstrated that Quercetin significantly increased the expression of ESR1 in HT‐29 colon cancer cells 59 . Calycosin promoted the expression of ER‐α36, which is the main oestrogen receptor of ESR1, in macrophages 60 .…”
Section: Discussionmentioning
confidence: 98%
“…demonstrated that Quercetin significantly increased the expression of ESR1 in HT‐29 colon cancer cells. 59 Calycosin promoted the expression of ER‐α36, which is the main oestrogen receptor of ESR1, in macrophages. 60 Kaempferol notably promoted ESR1 expression in the ovaries tissue of rats with premature ovarian failure.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, recent studies have reported that bisphenol A (BPA) may have toxic effects on the body and colon. Quercetin and its fermented extract exhibited excellent inhibitory effect on the viability of BPA-exposed HT29 colon cancer cells [33]. Additionally, quercetin enhanced the chemotherapeutic impact of oxaliplatin in HCT116 cells by increasing intracellular ROS through its suppressive action on glutathione levels [34].…”
Section: In Vitromentioning
confidence: 99%